Use of intravenous immunoglobulins in treatment of lupus psychosis : a case report (Annals of Medical Research, 2021)
Systemic Lupus Erythematosus (SLE) is a multisystem autoimmune disease. Its manifestations are protean and virtually any organ system can be involved. The disease in children is generally more acute and more severe than that in adult.Recently it has been notified that intravenous immunoglobulins (IVIG) in patients with cerebral lupus have improved fairly. In this report, we present a case of systemic lupus erythematosus involving multiple organ systems, including psychosis which did not respond to high-dose intravenous corticosteroid therapy. After application of IVIG (400 mg/kg/24 hr, 5 day/month) as an adjunctive agent, psychosis of the patient was completely improved. This report supports the finding that IVIG therapy may successfully be used for nonresponders to conventional treatments of SLE, especially for those with cerebral complications.
Keywords: Systemic Lupus Erythematosus, immunoglobulins, child.